Lived Experiences and Competencies of Out-of-Field Teachers in Teaching Filipino in Tboli West District: Basis for Developing a Suitable Program for Guidance and Support in Innovative Teaching Practices - FLANG, WILBERT; Magindra, Anesa (International Journal of Arts, Sciences and Education, 2025)
Out-of-field teaching, where teachers handle subjects outside their specialization, poses a challenge to the quality of education. This study aimed to examine the experiences, perspectives, and competencies of out-of-field teachers teaching Filipino and to develop a training program that addresses their needs. The research employed an exploratory sequential mixed-method approach, analyzing data from fifteen (15) teachers in the Tboli West District using a classroom observation tool rating and interviews. The study identified key themes describing their experiences, including fulfilling personal aspirations and social roles, challenges in teaching Filipino, personal growth and transformation in teaching Filipino, and the development of teaching skills and proficiency in the Filipino language. Additionally, the study determined themes that describe the context of their teaching experiences, such as positive emotional impact, acceptance of challenges and instructional improvement, and emotional and mental struggles in teaching Filipino. Findings also revealed that these teachers maintain a positive outlook on their professional future and continuously strive to enhance their teaching competencies. Moreover, the PAGSIK training program was developed and validated, receiving high validity and acceptance, reflecting strong approval and positive perception from experts. This study highlights the crucial role of sufficient support and training in improving the teaching effectiveness of out-of-field teachers.